MOSQUITO REPELLENTS FROM ESSENTIAL OILS OF PLANTS FROM FRENCH POLYNESIA - Vahirua-Lechat, I.; Adam, F.; Deslandes, E.; Bernier, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Filariasis and Dengue Fever are two mosquito-borne diseases threatening French Polynesia. The potential vectors for the transmission of these illnesses are Aedes aegypti (L.), the Yellow Fever mosquito, and A. polynesiensis Marks. A research program financed by the Ministry of Health of French Polynesia, the Establishment for Prevention and the Laboratory of Ecophysiology and Biotechnology of Halophytes and Marine Algae was undertaken with the ultimate goal of developing improved insect repellents and lures for insect traps. This goal became even more urgent due to the threat of mosquito-borne diseases. Several natural products from terrestrial plants of French Polynesia were evaluated as spatial repellents against A. aegypti mosquitoes, using a triple cage-dual port olfactometer, and as topical repellents, using a cloth patch assay test with DEET as the positive control. The attraction of A. aegypti to L-lactic acid combined with the natural sample extracts was evaluated using the dual-port olfactometer. A total of 10 aromatic plant species have been collected by the Laboratory of Natural Products of the Institute Louis Malardé, and these have yielded 10 Essential Oils. 4 more samples of essential oils originating from New Caledonia and Madagascar were also tested. The fine chemical composition of some repellent essential oils were determined by gas chromatography and gas chromatography coupled with Mass Spectrometry at Malardé and at Montpellier. Their major volatile components are still to be tested and the preliminary results are presented. Bioassays were performed with Ae. aegypti mosquitoes at the U.S. Department of Agriculture-Agricultural Research Service (USDA-ARS). This mosquito is the commonly accepted standard species for laboratory bioassays. Bioassays were conducted in randomized sample order and were distributed among the three cages of the olfactometer over three separate assay periods per day (approximately 08.00, 11.00, and 13.00 local time). Each sample was analyzed at least 3 times to improve the statistical precision of the results. The cloth patch repellency assays were conducted using 5-6 individuals to provide adequate precision of the duration and minimum effective dosage measures of the repellent efficacy.